Integrating Spatial Planning, Crisis Communication, and Support Facilities Into Family Assistance Centre Governance for Aviation Disaster Preparedness - Dinda Kharisha; Hayati Sari Hasibuan; Widura Imam Mustopo (Riviera Publishing, 2026)
This study aims to examine the governance and effectiveness of FAC preparedness at Airline X in Indonesia by focusing on three operational dimensions: spatial configuration, communication strategies, and support facilities. This research used a qualitative case study approach. Data were collected through in-depth interviews with airline personnel, government agencies, emergency service providers, and trained FAC personnel, supported by focus group discussions and document review. The data were analyzed using thematic analysis based on Miles and Huberman’s framework, while spatial syntax analysis was applied to examine the layout, accessibility, and functional suitability of proposed FAC locations at Soekarno-Hatta International Airport. Findings: The findings show that FAC readiness is shaped by the suitability of physical space, integrated multi-stakeholder communication, and adequate support infrastructure to ensure privacy, emotional care, family briefing, registration, information delivery, and logistical coordination. The study also found that Airline X’s FAC preparedness remains stronger at the planning and documentation level than at the operational capability level, particularly due to limited recurrent training, simulation, and practical experience in large-scale aviation emergency response. These findings are consistent with emergency management and organizational resilience perspectives, which emphasize that effective preparedness requires not only formal procedures but also trained personnel, coordinated roles, reliable communication systems, and operationally ready infrastructure. This study concludes that FAC governance should be institutionalized as an integral part of airline Emergency Response Plans through clearer procedures, regular exercises, defined coordination mechanisms, and facility standards aligned with family assistance principles.